SOSIALISASI MEMBANGUN KOPERASI DALAM MENDUKUNG PEREKONOMIAN MASYARAKAT DESA PURBA DOLOK SANGGUL KABUPATEN HUMBANG HASUNDUTAN - Donna Maryati Panggabean; Dahlia Nopelina Siallagan; Hotlin Siregar; Niarita Bukit (PKM Maju UDA, 2022)
This community service is carried out with the topic of building cooperatives in supporting the economy of rural communities. Dolok Purba Village has a very potential area in the agricultural sector. The village of Purba Dolok also has a cooperative that is able to accommodate agricultural products from the village community and act as a facilitator for agricultural needs. However, the cooperative's activities have not been going well because the processing system is not optimal. For this reason, the presenters were very interested in doing community service on the topic "Building cooperatives in the cloudy economy of the people of the ancient village of Dolok Sanggul, Humbang Hasundutan Regency", with the aim that the community is aware of the importance of cooperatives for the economy of the people in the village. The speakers and the team presented material topics about the meaning of cooperatives, types of cooperatives, procedures for forming cooperatives and then motivated the community that cooperatives are very helpful in improving people's welfare. The methods used in the implementation of this community service are Observation, Interview and Discussion. The lecture method is through delivering presentations by displaying pictures, videos and displays that are attractive and easy to understand so that they can attract the attention of participants so that they are active in discussions. This community service is carried out with socialization and ends with a question and answer system regarding the material presented and the implementation that took place in the community of the Purba Dolok Sanggul village. Before starting the socialization, the presenters asked the participants about their jobs, whether they had become members of the cooperative. It turned out that there were some participants who did not know about cooperatives, the benefits of cooperatives, and had not become members of cooperatives and did not know how to become members of cooperatives. By holding this counseling, it is hoped that the ancient village community will understand more about what cooperatives are, the role of cooperatives and are willing to become cooperative members so that the development of cooperatives in the ancient village of Dolok Sanggul becomes even more advanced.